Pneumocephalus: an unusual cause - D'Addario, Richard (1974)
A 60 year old male had an open thoracotomy for bronchogenic carcinoma. On the twelfth hospital day he became obtunded and complained of headache. Radiographs revealed intracranial air. It was thought that the pneumocephalus in this patient was most likely secondary to a tension pneumothorax continuously forcing air through a dural tear sustained at the time of initial surgery. The causes of pneumocephalus are reviewed and no similar case report has been found in the literature.